Validity of Sinonasal Outcome Test 22 in Assessing Symptomatological Outcome Following Septoplasty in Deviated Nasal Septum - Bhandari, Shama; Paudel, Dhundi Raj; Mahaseth, Subhash (Journal of Nepalgunj Medical College, 2022)
Introduction: Nasal obstruction is the most common symptom of deviated nasal septum. Septoplasty is a surgical procedure that corrects deformity of the nasal septum. Sinonasal outcome test 22 is a subjective questionnaire tool that include various nasal symptoms which is useful to measure patient`s symptoms outcome after septoplasty. Aims: To determine the symptomatologic outcome in patients with deviated nasal septum following septoplasty using Sinonasal outcome test 22. Methods: This prospective longitudinal study was done atNepalgunj Medical College and Teaching Hospital, Kohalpur including 60 patients of symptomatic deviated nasal septum who underwent septoplasty. Details of patient symptoms as per Sinonasal outcome test - 22 were graded from zero to five preoperatively and were compared one month following surgery. Results: Patients who underwent septoplasty were commonly in the age group 20-45 years and least in the age group 46-60 years with a mean age of 25.48. In the present study, the male to female ratio was 1.4:1. Deviated nasal septum was more common on the left side (53.3%). The mean preoperative sinonasal outcome test -22 score was 24.42 (range 14-40), and the mean postoperative sinonasal outcome test-22 score was 12.93 (range 8-23) and the difference was 11.49. Conclusion: Sinonasal outcome test 22 is a subjective questionnaire tool used in patients with deviated nasal septum. In our study with the use of this questionnaire tool there was improvement in nasal symptoms on comparing preoperative and postoperative symptoms following septoplasty.